ANALISIS STRUKTUR MOORING DOLPHIN KAPASITAS KAPAL 2000 GT (STUDI KASUS PELABUHAN MUNSE SULAWESI TENGGARA) - Edward Hafudiansyah; An An Anisarida (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2021)
Sea transportation is the main transportation used by residents in the islands. The development of marine transportation facilities is expensive to support these activities. Therefore, several alternatives are needed to streamline construction costs, one of which is the construction of a pier using a mooring dolphin. The purpose of this study is to calculate the structural strength of the mooring dolphin with a ship capacity of 2000 GT at Munse Port, Southeast Sulawesi Province. Structural analysis is carried out by analyzing pile capacity and joint displacement analysis. The calculation of the strength of the pile elements at the pier was analyzed using the SAP 2000 program. For soil which is modeled as an elastic support, the ability to support the load depends on the magnitude of the modulus of subgrade reaction from the soil. Embedded pile modeling is modeled with a nonlinear spring force. The results of the analysis by analyzing the capacity of piles with dimensions of 508 mm with a thickness of 12 mm resulted in a capacity ratio of 0.72. The results of the analysis of joint displacement in service or operational conditions are 37.09 mm and in earthquake conditions, they are 13.01 mm.